2023
DOI: 10.1111/andr.13409
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA damage: The possible link between obesity and male infertility, an update of the current literature

Abstract: Obesity prevalence worldwide is increasing significantly. Whilst maternal obesity has clear detrimental impacts on fertility, pregnancy and foetal outcomes, more recently there has been an increasing focus on the role of paternal obesity in human fertility. Recent meta‐analyses have indicated that obesity in men negatively affects basic sperm parameters such as sperm count, concentration and motility, increases the incidence of infertility and reduces the chances of conception. Sperm DNA damage, typically char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 187 publications
(332 reference statements)
0
4
1
Order By: Relevance
“…The low sample number ( N = 118 samples from 29 men) also likely contributed to the weak to moderate strength associations between biological and lifestyle factors and measures of both basic and extended semen parameters, with some correlations going in the opposite direction to that expected. For instance, BMI was weakly negatively associated with sperm DNA damage and lipid peroxidation a direct opposite to that of the current literature [ 32 ]. Whilst other relationships correlated as expected, such as sperm DNA damage and lipid peroxidation both positively correlating with abstinence, a factor which is known to increase sperm oxidative stress [ 38 ].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The low sample number ( N = 118 samples from 29 men) also likely contributed to the weak to moderate strength associations between biological and lifestyle factors and measures of both basic and extended semen parameters, with some correlations going in the opposite direction to that expected. For instance, BMI was weakly negatively associated with sperm DNA damage and lipid peroxidation a direct opposite to that of the current literature [ 32 ]. Whilst other relationships correlated as expected, such as sperm DNA damage and lipid peroxidation both positively correlating with abstinence, a factor which is known to increase sperm oxidative stress [ 38 ].…”
Section: Discussioncontrasting
confidence: 79%
“…We observed only weak to moderate associations likely due to our low sample size (a limitation of our pilot trial), which were consistent with those previously reported in the literature. For instance, we found negative associations between traditional sperm parameters of count, motility, and morphology with age [ 30 ], BMI [ 31 , 32 ], waist circumference [ 33 , 34 ], and general health and psychological wellbeing [ 35 ]. Dietary intake, which displayed the biggest variations across collections in our cohort, was also associated with semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…In males, a meta-analysis suggests a signi cant correlation between increased BMI and decreased seminal volume, sperm count, concentration, and viability [34]. Additionally, in animal studies, obesity is correlated with increased sperm DNA damage, but ndings in human studies are inconsistent in this regard [35]. The abnormal lipid pro le in obese males may lead to testicular oxidative stress, which is a common pathway for disruption in sperm function [36].…”
Section: Discussionmentioning
confidence: 99%
“…One of many potential causes of oxidative stress with the male reproductive system is the global pandemic in obesity. In this Special Issue, Peel et al 20 summarized the latest animal and human data suggesting that obesity is associated with an increase in sperm DNA damage via a range of direct and indirect mechanisms. These authors highlight the potential role of oxidative stress in not only mediating the impact of obesity on sperm DNA damage, but also in the transgenerational inheritance of obesity.…”
Section: Management Of Sperm Dna Damagementioning
confidence: 99%
“…One of many potential causes of oxidative stress with the male reproductive system is the global pandemic in obesity. In this Special Issue, Peel et al 20 . summarized the latest animal and human data suggesting that obesity is associated with an increase in sperm DNA damage via a range of direct and indirect mechanisms.…”
Section: Management Of Sperm Dna Damagementioning
confidence: 99%